Auctions vs. negotiations: The case of favoritism - Vitali Gretschko; Achim Wambach (Center for Economic Studies and ifo Institute (CESifo), 2012)
We compare two commonly used mechanisms in procurement: auctions and negotiations. The execution of the procurement mechanism is delegated to an agent of the buyer. The agent has private information about the buyer's preferences and may collude with one of the sellers. We provide a precise definition of both mechanisms and show - contrary to conventional wisdom - that an intransparent negotiation yields a higher buyer surplus than a transparent auction for a range of parameters. In particular, for small expected punishments there exists a lower and an upper bound on the number of sellers such that the negotiation yields a higher buyer surplus with a probability arbitrary close to 1 in the parameter space. Moreover, if the expected punishment is small, the negotiation is always more efficient and generates a higher surplus for the sellers.
Keywords: D44; D73; L13; H57; 330; corruption; auctions; negotiations; public procurement; Öffentliche Beschaffung; Verhandlungen; Auktion; Lieferanten-Kunden-Beziehung; Asymmetrische Information; Korruption; Wohlfahrtsanalyse; Theorie